FACTORS INFLUENCING HEALTH BEHAVIOR AMONG TYPE 2 DIABETES MELLITUS PATIENTS: AN INTEGRATIVE REVIEW - Kusuma Wijaya Ridi Putra; Chanandchidadussadee Toonsiri (Belitung Nursing Journal, 2017)
Objective: This integrative review aims to summarize and identify the current literature related to health behavior among Type 2 Diabetes Mellitus (T2DM) Patients and its factors. Methods: An integrative review was undertaken using literature published between 2000 and 2013, based on CINAHL, Springer link, PubMed, Science Direct and Google Scholar. Results: Twenty-two articles were selected based on inclusion and exclusion criteria. This review indicated a wide range of factors influencing health behavior among T2DM patients including predisposing factors (socioeconomic, knowledge, stress management, and health belief), reinforcing factor (family support), and enabling factor (health service). Conclusion: Family support, socioeconomic and knowledge are the significant major factors of health behavior among T2DM patients. However, the others factors such as stress management, health belief and health service are also the important factors for T2DM patient’s health behaviors. Therefore, these factors should be considered for development of appropriate interventions to promote health behavior among T2DM patients at community.